Insights into pancreatic β cell energy metabolism using rodent β cell models [version 3; peer review: 2 approved, 1 not approved] - Karl J Morten; Michelle Potter; Luned Badder; Pamela Sivathondan; Rebecca Dragovic; Abigale Neumann; James Gavin; Roshan Shrestha; Svetlana Reilly; Kanchan Phadwal; Tiffany A. Lodge; Angela Borzychowski; et al. (Wellcome Open Research, 2019)
Background: Mitochondrial diabetes is primarily caused by β-cell failure, a cell type whose unique properties are important in pathogenesis. Methods: By reducing glucose, we induced energetic stress in two rodent β-cell models to assess effects on cellular function. Results: Culturing rat insulin-secreting INS-1 cells in low glucose conditions caused a rapid reduction in whole cell respiration, associated with elevated mitochondrial reactive oxygen species production, and an altered glucose-stimulated insulin secretion profile. Prolonged exposure to reduced glucose directly impaired mitochondrial function and reduced autophagy. Conclusions: Insulinoma cell lines have a very different bioenergetic profile to many other cell lines and provide a useful model of mechanisms affecting β-cell mitochondrial function.